Hand hygiene compliance of health care workers in a neonatal intensive care unit: a prospective observation study - Alci, Gamze; Bilgen, Hulya; Ozek, Eren; Yagci, Aysegul Karahasan (International Journal of Research in Medical Sciences, 2021)
Background: We aimed to determine hand hygiene (HH) compliance of the healthcare workers (HCW’s) and evaluate if there is an epidemiological relation between the microorganisms isolated from the hands of HCWs and patients clinical materials in the neonatal intensive care unit (NICU). Methods: HH compliance was observed in two unannounced phases in March and in August within the scope of 5 indications determined by WHO. Between two phases personnel was trained to improve HH by educational sessions and introduction of Semmelweis system hand in scan (HIS, Sysmex) in the unit. A total of 22 nurses, 11 physicians and 5 staff was working in the NICU. Hand samples taken from HCW by glove juice method were inoculated quantitatively in culture plates and colonies were identified by MALDI-TOF MS. Epidemiological relation between clinical isolates and hand samples was investigated with arbitrary primed PCR. Results: Although overall compliance remained only 50%, a significant increase in compliance was detected in August prior to aseptic procedures and after contact with patients and body fluids. Alcohol scrub was preferred as 60.4% in March and 75.2% in August. HH efficacy reached to 72% by implementing HIS. During this period, 10.7% of 607 patient’s samples revealed clinically significant growth. Potential pathogens were isolated in 5.2% of 144 hand samples, but any epidemiological correlation with patient isolates was detected. Conclusions: HH compliance observations should be done at regular intervals and current technology could be utilized in trainings to overcome hospital related infections.